If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(m + 3) = 3(m + 4) + m Reorder the terms: 4(3 + m) = 3(m + 4) + m (3 * 4 + m * 4) = 3(m + 4) + m (12 + 4m) = 3(m + 4) + m Reorder the terms: 12 + 4m = 3(4 + m) + m 12 + 4m = (4 * 3 + m * 3) + m 12 + 4m = (12 + 3m) + m Combine like terms: 3m + m = 4m 12 + 4m = 12 + 4m Add '-12' to each side of the equation. 12 + -12 + 4m = 12 + -12 + 4m Combine like terms: 12 + -12 = 0 0 + 4m = 12 + -12 + 4m 4m = 12 + -12 + 4m Combine like terms: 12 + -12 = 0 4m = 0 + 4m 4m = 4m Add '-4m' to each side of the equation. 4m + -4m = 4m + -4m Combine like terms: 4m + -4m = 0 0 = 4m + -4m Combine like terms: 4m + -4m = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 4X^2-3x-18=x^2 | | -5(x+1)-15=11+4 | | 17-(x-4)=-8-9 | | 12b-11-b-9= | | 8x^2+24x-16=0 | | 4(x-2)=5-(x+1)-5 | | 7a/-8=-23 | | 6(3x-5)=3(6x+1) | | 2x^2+35x+27=0 | | 24/.15 | | (3tan^-1(3/4y))^2 | | 4/7b-3=12 | | m=4m+4w | | 5a-3a=1+205 | | 2-k/-7=11 | | 11(v+4)-2v=3(3v+4)-15 | | 66=x+(2x+3) | | f(x)=x^2-7x+4 | | (3x)x=320 | | 8.3+9x=8.5 | | 2(16+y)-8+5y=16 | | 5-4y+y-1=-22 | | 2(x-5)=6-(x+7)-3 | | 4+7=95 | | p=12-2D | | (5x-2)x=18 | | h(2h+5)=52 | | P=12-2Qd | | -6n+8=-4n+10 | | 10y-3= | | -5(n-5)-(3n-1)=-3+(6n-6) | | x^2+44=188 |